The Forty-second Annual ISNA Convention (American Journal of Islam and Society, 2005)
The theme of this year’s event, “Muslims in North America: Accomplishments,Challenges, and the Road Ahead,” was a public proclamation thatNorth American Muslims are focusing on the future. One highlight was thepresence of Undersecretary of State for Public Diplomacy Karen Hughes,who met with heads of Muslim American organizations on the grounds thatshe needed their advice to help her reach out to the wider Muslim world.Overall, the convention focused on advancing values of the family, community,compassion, and justice; the workshops addressed communitybuilding, organizing politically, promoting civil rights, opposing Islamophobia,sharing Islam, and promoting interfaith understanding.The conference was inaugurated by the leaders of ISNA’s constituentorganizations and leaders of other faiths. Bob Edgar (secretary general,National Council of Churches), set the tone: “If you want to walk fast,walk alone. If you want to walk far, walk together!” Muhammad NurAbdullah (president, ISNA) spoke of such ISNA accomplishments as theimam and chaplain training services and empowering Muslim youths. Theinaugural session was addressed by Khurshid A. Qureshi (president,AMSE) Rafik Beekun (president, AMSS), Rehana Kausar (president,IMANA), Mohammad Sheibani (president, MSA), and co-chairs OmarSiddiqi and Kulsoom Salman (both of MSA-National). Ingrid Mattson(vice president, ISNA; director, Islamic chaplaincy; and professor, Islamicstudies and Christian-Muslim relations, Hartford Seminary), Abdul-MalikMujahid (president, Council of Islamic Organizations of Greater Chicago),Bob Edgar (secretary general, National Council of Churches), and RickUfford-Chase (chair of the moderator of the 216th General Assembly ofthe Presbyterian Church [USA]).The ISNA Dr. Mahboob Khan Community Service Award was presentedto Ilyas Ba-Yunus, a founding member of MSA who helped establishISNA and served as its first president. A respected sociologist, he is theauthor of several studies related to Muslim life in America. FormerMalaysian deputy prime minister Anwar Ibrahim, the keynote speaker at theCommunity Service Recognition luncheon, expressed his gratitude forISNA’s role in securing his release after the charges brought against him byformer prime minister Mahathir Muhammad failed the court test. In keepingwith a now 3-year-old tradition, Anwar received an award recognizing hiscontribution to democracy, civil society, and social justice ...